Analisis penggunaan Media sosial untuk pembelajaran Kewirausahaan di kantin sekolah siswa MTs Almadinah Ambon - Nurul 'Ainy, Zuhria; Nahla, Zahro Tun (Universitas Hamzanwadi, 2024)
This research aims to analyze the use of social media for entrepreneurship learning in the school canteen of MTs Almadinah Ambon students. This research uses qualitative methods with data collection techniques through observation, interviews and document analysis. The samples for this research were students and teachers at MTs Almadinah Ambon who used social media as part of entrepreneurship learning in the school canteen. Data were analyzed using a thematic approach to identify patterns of social media use in the context of entrepreneurship learning. The research results show that the use of social media in the school canteen of MTs Almadinah Ambon students has a positive impact on entrepreneurship learning. Students experience increased motivation and involvement in learning through interactions that occur on social media. In addition, teachers also report the use of social media as an effective tool in developing students' social and critical skills in understanding entrepreneurial concepts. In conclusion, the use of social media in entrepreneurship learning in the school canteen of MTs Almadinah Ambon students has the potential to improve students' learning experiences and expand the learning space outside the classroom